How The Role of Digital Marketing and Brand Image on Food Product Purchase Decisions? An Empirical Study on Indonesian SMEs in the Digital Era - Purwanto, Agus (Journal of Industrial Engineering & Management Research, 2022)
This empirical research aims to test and prove the effect of marketing strategy through digital marketing on purchasing decisions and the brand image variable is a mediation. Data were collected using a sampling technique where 320 respondents transacted in Indonesian SMEs. This research method is a quantitative method through path analysis and data analysis using SPSS software. The research data was obtained using a Likert scale questionnaire distributed online. Based on the results of multiple linear analysis and Sobel test, it shows that digital marketing has a positive and significant effect on purchasing decisions and brand image as a moderating variable can strengthen or increase the influence of Digital Marketing variables on purchasing decision variables.